Loofah-based microalgae and cyanobacteria biocomposites for intensifying carbon dioxide capture. Issue 42 (December 2020) - In-na, Pichaya; Umar, Abbas A.; Wallace, Adam D.; Flickinger, Michael C.; Caldwell, Gary S.; Lee, Jonathan G.M.
Highlights: Biocomposites to remove CO2 were made from algae, latex binders and loofah sponge. CO2 fixed at 0.12–0.93 gCO2 g -1 biomass d -1, which is 5–10 times rate of suspension controls. Polymer film makes the biocomposites mechanically robust, preventing contamination. Useful metabolites were recoverable at end of life, for example up to 70 % lipid by weight. Abstract: Microalgae and cyanobacteria have been evaluated for biological CO2 capture from flue gases for over 40 years; however, commercial open ponds and photobioreactors suffer many drawbacks including a slow rate of CO2 capture and high water usage. We evaluate an intensified 3D cell immobilisation approach with a small water demand, by coating latex binders onto defined surface area (947 m 2 m −3 ) and void space (81.78 ± 4.41 %) loofah sponge scaffolds, forming porous 3D biocomposites with three microalgae species; freshwater Chlorella vulgaris, marine Dunaliella salina and Nannochloropsis oculata, and two strains of freshwater Synechococcus elongatus cyanobacteria. Binder toxicity and adhesion screening protocols were established ahead of eight weeks semi-batch and six weeks continuous CO2 fixation trials. Acrylic and polyurethane binders were effective for microalgae, and bio-based (Replebin®) binders were suited for cyanobacteria. The highest average net CO2 fixation rates from each species were 0.17 ± 0.01, 0.25 ± 0.01, 0.12 ± 0.01, 0.68 ± 0.18 and 0.93 ± 0.30 g CO2 g -1 biomass d -1 for C. vulgaris, D. salina, N. oculata, S. elongatus PCC 7942 and S. elongatus CCAP 1479/1A respectively. This equates to predicted CO2 capture from scaled systems of up to 340.11 ± 110 tCO2 t -1 biomass yr -1 . Analysis of the kinetics of CO2 absorbtion and SEM imaging suggests that the cells were embedded within a polymer film that covered the scaffold. Biocomposites continuously fed with 5% CO2 had high lipid contents approaching 70 % dry weight. This biocomposite approach shows promise to intensify biological CO2 capture and possible application in bioenergy with carbon capture and storage (BECCS).